Cuban scientific production on diabetes, 2000–2017: Peer-reviewed Publications, Collaboration and Impact - Corrales-Reyes, I.E. (2019)
INTRODUCTION The steadily increasing prevalence of diabetes globally has captured researchers’ attention. Cuban production of scientific articles on diabetes has not been studied from a bibliometric perspective. OBJECTIVE Characterize the production and impact of research and review articles on diabetes by Cuban authors in journals listed in the Scopus bibliographic database, as well as related collaboration among Cuban institutions and between Cuban and non-Cuban institutions. METHODS A bibliometric analysis was conducted using 2000–2017 data from the Scopus database. The following search strategy was used: descriptor (diabetes), country (Cuba), publication source (journal), article type (original research, review article). Bibliographic indicators of production, visibility, impact and collaboration were examined.